Seismic Vulnerability Assessment of Bergama Bedesten - Aktaş, Engin; Demir, Hatice Ayşegül; Hamamcıoğlu Turan, Mine (Izmir Institute of Technology, 2022)
This study aims to document Bergama Bedesten with emphasis on its construction technique and material usage; and assess its structural condition for future seismic action through numerical analysis. The monument (15th -16th century) is unique among the historical trade buildings at the center of Bergama, İzmir. It is revealed that the structure is a rare example by the use of plane triangles as transition elements, the oculi placement in domes, and the thickening application at parts where load-bearing arches integrate into the walls and at the corners. In order to investigate the vulnerability of the building, numerical analysis using the finite element method was conducted in ANSYS software. According to the Turkey Building Earthquake Code (2018), single-mode equivalent earthquake analysis considering the horizontal elastic design spectrum of the site was carried out for x and y directions, separately. The maximum principal stress concentration locations obtained through analyses point vulnerable zones. These were specifically observed on load-bearing arches, on some plane triangles, on the transition zones, at dome parts close to the transition zone and peak level, at the parts where arches integrate to the walls, around top windows, on the west entrance door arch, and on a secondary door arch in the north wall. The method comparing the structural failure mapping and visual structural alterations analysis of architectural restoration with finite element model results, emphasizes that some damaged or altered portions in the current state are in seismically vulnerable spots. Some precautions, further studies and interventions were suggested for these locations.

Bu çalışma, Bergama Bedesteni’ni yapım tekniği ve malzeme kullanımıyla birlikte belgelemeyi ve gelecekte oluşabilecek deprem yükleri için kapasitesini nümerik analizlerle değerlendirmeyi amaçlamaktadır. Anıt (15.-16. yüzyıl) İzmir’in bir ilçesi olan Bergama’nın merkezinde tarihi ticaret yapıları arasında özgündür. Strüktürün düzlem üçgenlerin geçiş elemanı olarak kullanılması, kubbelerdeki filgözü tasarımı, taşıyıcı kemerlerin duvarlarla bütünleştiği kısımlarda ve köşelerde kesitte kalınlaştırma uygulamalarıyla ender bir örnek olduğu ortaya çıkarılmıştır. Yapının hasar görebilirliğini araştırmak için ANSYS yazılımı kullanılarak sonlu elemanlar yöntemiyle nümerik analizler yapılmıştır. Türkiye Bina Deprem Yönetmeliği'ne (2018) göre, x ve y yönleri için ayrı ayrı olarak yapı arazisinin yatay elastik tasarım spektrumu dikkate alınarak tek modlu eşdeğer deprem yükü analizi gerçekleştirilmiştir. Analizler sonucunda elde edilen maksimum asal gerilmelerin yoğunlaştığı bölgeler hasar görebilir kısımları gösterir. Bu kısımlar özellikle taşıyıcı kemerlerde, bazı düzlem üçgenlerde, geçiş kuşağında, bazı kubbelerin geçiş kuşağına ve tepe noktasına yakın kısımlarında, kemerlerin duvarla bütünleştiği bölümlerde, tepe penceresi açıklıklarının çevresinde, batı giriş kapısı kemerinde ve kuzey duvarına sonradan eklenen kapı açıklığı kemerinde gözlenmiştir. Strüktürel hasar ve görsel strüktürel değişimler analizi sonuçlarını sonlu elemanlar modeli sonuçlarıyla karşılaştıran yöntem, bazı hasar görmüş ya da değişmiş kısımların mevcut durumda sismik açıdan hasar görebilir bölümlerde olduğunu vurgular. Bu bölümler için bazı önlemler, ileri çalışmalar ve müdahaleler önerilmiştir.
Bergama Bedesten'nin Sismik Hasar Görebilirliğinin Değerlendirilmesi
Thesis (Master)--Izmir Institute of Technology, Architectural Restoration, Izmir, 2022
Includes bibliographical references (leaves. 154-161)
Text in English; Abstract: Turkish and English
Keywords: Bergama Bedesten; Seismic vulnerability assessment; Structural analysis (Engineering)